Cool, caring and communicating - the human touch: How car brands used social media anthropomorphism in pandemic times - Rohit Tiwari; Tanuj Negi; Supriya Chouthoy (Rajagiri Management Journal (RAMJ), 2025)
This study aims to examine the influence of Brand Anthropomorphism on Conversational Value and Attitude Towards Communication (relevance) of Gen Y and Gen Z consumers in the context of the COVID-19 pandemic. The study considered interactive marketing strategies used by premium auto brands on social media during this crisis and their impact on consumers. Keeping consumers engaged with brands was a challenge during the pandemic and the premium auto brands in the study ensured that anthropomorphic brand communication, created conversations about the brand.This primary study used a structured questionnaire to collect data from 102 respondents who witnessed changes in logos by two premium automotive brands on social media platforms during the COVID-19 pandemic. The dataset was analysed using the partial least squares - structural equation modelling methodology and the multi-group analysis (MGA) procedure.The study reveals that brand anthropomorphism affects consumer's attitude and encourages consumer conversations. Mass media was employed to raise public awareness and increase the receptivity to learning certain social behaviours during the pandemic. The auto brands in this study also effectively engaged with consumers about such behaviours through their logos which had consumers communicating with the brand as well as amongst themselves.The study used convenience sampling and an online survey format, which may limit the breadth and representativeness of responses. Future research could adopt probabilistic sampling methods, broaden participant diversity, and extend the analysis to other sectors such as fast-moving consumer goods, hospitality and e-commerce. Expanding the model to include constructs such as brand image and purchase intent, as well as exploring cross-cultural dynamics and the longer-term impact of anthropomorphic branding, would offer a more comprehensive understanding of how such strategies influence consumer perceptions and behaviour during crises.From a managerial perspective, the results underscore the strategic value of anthropomorphic communication in customer engagement, particularly on digital and social platforms where interaction is frequent and public. The significant and consistent positive effects across brands suggest that brand managers can confidently implement anthropomorphic cues such as conversational tone, human-like avatars, personalised messaging style or emotionally expressive language to cultivate more favourable attitudes toward brand communication and increase the perceived worth of brand consumer exchanges.The study aims at contributing to the body of knowledge as it investigates a unique the correlation of brand anthropomorphism with conversational value and attitude towards the communication by the brand. This study provides empirical evidence in support of the Stereotype Content Model in the context of premium automotive brands.
Keywords: 650; Brand anthropomorphism; Social media marketing; Brand communication; COVID-19 advertising; Crisis marketing